Simultaneous first language acquisition: a window on early grammatical development - Meisel, Jürgen M. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
From the perspective of principle and parameter theory, the simultaneous acquisition of the first two languages requires the child to be able to set a parameter twice, in the same way. be the opposite way. This work focuses on the placement of the verb in the acquisition of German and French, in which the two languages differ substantially, involving various properties. The work corroborates the predictions of the Structure Construction Theory, according to which children have no access to functional categories in the primary stages. The acquisition of these depends on the implementation of new features in initially under-specified categories. The comparison of the results with what occurs in monolingual acquisition of French and German also shows that the grammar of bilingual children is the same as monolingual grammar at each stage of development, with no evidence, even temporary, of grammar fusion.